Cytotoxic mechanism of sphaerodactylomelol, an uncommon bromoditerpene isolated from sphaerococcus coronopifolius - Alves, Celso (2021)
Marine natural products have exhibited uncommon chemical structures with relevant antitumor properties highlighting their potential to inspire the development of new anticancer agents. The goal of this work was to study the antitumor activities of the brominated diterpene sphaerodactylomelol, a rare example of the dactylomelane family. Cytotoxicity (10–100 M; 24 h) was evaluated on tumor cells (A549, CACO-2, HCT-15, MCF-7, NCI-H226, PC-3, SH-SY5Y, SK-ML-28) and the effects estimated by MTT assay. Hydrogen peroxide (H2O2) levels and apoptosis biomarkers (membrane translocation of phosphatidylserine, depolarization of mitochondrial membrane potential, Caspase-9 activity, and DNA condensation and/or fragmentation) were studied in the breast adenocarcinoma cellular model (MCF-7) and its genotoxicity on mouse fibroblasts (L929). Sphaerodactylomelol displayed an IC50 range between 33.04 and 89.41 M without selective activity for a specific tumor tissue. The cells’ viability decrease was accompanied by an increase on H2O2 production, a depolarization of mitochondrial membrane potential and an increase of Caspase-9 activity and DNA fragmentation. However, the DNA damage studies in L929 non-malignant cell line suggested that this compound is not genotoxic for normal fibroblasts. Overall, the results suggest that the cytotoxicity of sphaerodactylomelol seems to be mediated by an increase of H2O2 levels and downstream apoptosis.